Outlier removal to uncover patterns in adverse drug reaction surveillance – a simple unmasking strategy. (7th July 2013) - Juhlin, Kristina; Ye, Xiaofei; Star, Kristina; Norén, G. Niklas
ABSTRACT Purpose This study aimed to develop an algorithm for uncovering associations masked by extreme reporting rates, characterize the occurrence of masking by influential outliers in two spontaneous reporting databases and evaluate the impact of outlier removal on disproportionality analysis. Methods We propose an algorithm that identifies influential outliers and carries out parallel analysis after their omission. It considers masking of drugs as well as of adverse drug reactions (ADRs), uses a direct measure of the masking effect and makes no assumptions regarding the number of outliers per drug or ADR. The occurrence of masking is characterized in the WHO Global Individual Case Safety Report database, VigiBase and a regional collection of reports from Shanghai, China. Results For WHO‐ART critical terms such as myocardial infarction, rhabdomyolysis and hypoglycaemia outlier removal led to a 25–50% increase in the number of Statistics of Disproportionate Reporting (SDR) and gains in time to detection of 1–2 years, while keeping the rate of spurious SDRs from the parallel analysis at 1%. Twenty‐three per cent of VigiBase and 18% of Shanghai SRS reports listed an influential outlier. Twenty‐seven per cent of the ADRs and 5% of the drugs in VigiBase, and 2% of the ADRs and 3% of the drugs in Shanghai SRS were involved in an outlier. The overall increase in the number of SDRs for both datasets was 3%. Conclusion Masking by outliers has substantial impact on specific ADRs including, in VigiBase, rhabdomyolysis, myocardial infarction and hypoglycaemia. It is a local phenomenon involving a fair number of reports but yielding a limited number of additional SDRs. Copyright © 2013 John Wiley & Sons, Ltd.